Closing yield gap for sustainable food security in Sub-Saharan Africa – progress, challenges, and opportunities - Ongoma, V.; Brouziyne, Youssef; Bouras, E. H.; Chehbouni, A. (Frontiers Media, 2025)
Sub-Saharan Africa (SSA) remains food insecure despite having a climatic and biophysical potential to grow the crops to meet its growing food demand. Closing yield gap presents an opportunity to increase agricultural productivity in SSA for food security and economic stability in line with SDG 2 and 1. This work looks into the three main drivers of yield gap in SSA: water, fertilizer, and management practices, pointing out the challenges and opportunities for closing the gap. Rainwater is a good source of water, especially in tropical areas, and there is a need for its harvesting and conservation. Fertilizer use is still low (~20 kg/ha), and has to be increased while managing fertilizer nutrients effectively supported by locally developed computer-based decision support systems, for high crop yields. Latest commitments by African Union to increase local production, and supply, and reduce fertilizer costs is commendable. Adopting new crop varieties that are adapted to local conditions and resistant to drought and diseases, as well as improving good management practices backed by extension services are essential to maximizing crop yield and strengthening resilience in the face of environmental challenges. This calls for good leadership, backed up with good policies and political goodwill.